Phenotypic intrafamilial variability of 5q-associated spinal muscular atrophy: a systematic multicentre sibling study - Becker, Benedikt; Cordts, Isabell; Becker, Jutta; Günther, Rene; Baumann, Matthias; Bernert, Günther; Eisenkölbl, Astrid; Fiedler, Barbara; Flotats-Bastardas, Marina; Fleger, Martin; Hagenacker, Tim; Hahn, Andreas; et al. (Journal of neuromuscular diseases, 2025)
Background and objectives - The severity of the phenotype of spinal muscular atrophy (SMA) is highly variable, yet little is known about the phenotypic variation among siblings. We systematically investigated the phenotypic variability of therapy-naïve 5q-SMA siblings leveraging a large multicentre cohort from the SMArtCARE registry. - Results - Clinical information was available from 132 siblings of 65 families. There were 24 (18.2%) type 1, 38 (28.7%) type 2, 54 (40.9%) type 3 patients, and 16 (12.1%) presymptomatic individuals. In 17 families (32.1%), there was discordance in the type of SMA among symptomatic siblings. We found no influence of gender on discordance in SMA type among siblings (p = 0.528). The median age at disease onset within all sibships varied by 6 months (interquartile range (IQR) = 1-30). There was no correlation in age of onset among siblings (r = 0.405; p = 0.052). Among siblings who lost ambulation, the median interval between the start of wheelchair use was 12 months, but the maximal interval was 18 years. In one pair of siblings, one sibling lost the ability to walk at the age of 13, whereas the other sibling was still ambulatory at the age of 54. In 6 sibling pairs (9.5%), only one of both siblings had a history of scoliosis surgery. Analysing SMN2 copy numbers, in one sibling pair (1.8%) 1 SMN2 gene copy was detected, while 10 (17.5%) had 2 copies, 23 (40.4%) had 3 copies, and 17 (29.8%) had 4 copies. Concordance in SMN2 copy numbers across siblings was observed in 90% of families. With increasing SMN2 copy number, the median differences in age of onset among siblings increased without reaching statistical significance. - Conclusion - This study reports considerable phenotypic variability in therapy-naïve SMA sibships that cannot solely be explained by differences in SMN2 copy numbers.